Pengaruh Iklim Sekolah terhadap Tingkat Stres Siswa Sekolah Menengah Kejuruan Polimedik Depok - Siskandar Siskandar; Shunhaji Shunhaji; Ahmad Mulyono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
This study aims to determine and test empirical data related to school climate on student stress levels. In this study the authors used a quantitative approach through the survey method. The sample of this research is 69 students of vocational high school (SMK) Polimedik Depok. Data collection techniques using a questionnaire / questionnaire, observation, and documentary studies. The data analysis technique used is descriptive analysis, correlation coefficient, and simple regression analysis. The type of analysis used is simple correlation and regression analysis. The results of this study indicate that there is a negative and significant influence between the school climate and the stress level of students of SMK Polimedik Depok. This is known based on the results of the correlation coefficient of -0.502 and the coefficient of determination R-square of 0.250. The simple regression results show the equation Å¶ = 46.217 - 0.250 X2 which means that partially, if there is an increase in one unit of school climate score, it will affect the decrease in student stress level scores by 0.250